Pembuatan Edible film Pati Jagung dengan Penambahan Kitosan Sisik Ikan Papuyu (Anabas testudienus) - Yuli Ristianingsih; Maria Natalia (Jurnal Teknologi Agro-Industri, 2019)
Food packaging most used in order to keep the quality of food could be maintained to consumers. Plastic non-biogradable have weakness such as it is not degradable of environment and it is not safe to health because contain bhispenol. Edible film is solution for this problem because made of chitosan-starch. Starch is natural polymer that safe to use because easy to degradable, edible and economist. Corn starch contain high amylose content is 25%. Addition of chitosan could increase mechanical properties and barrier properties of edible film. The purpose of this research was to find out the effect of addition of chitosan on physiochemical properties edible film. Variation of chitosan used was 0,5; 1; 1,5 and 2 gram. The best result of solubility in water was addition chitosan 2 gram with value 49,74%.